Brumbie dust a selection of stories - Ottley, Reginald Leslie (New York Harcourt, Brace & World, 1969)
Nine stories about the wild horses of central Australia and the men who hunt them.
Brumbies -- The last of the horsemen -- Stampede -- Brush secret -- Dusty deal -- Brumbie running -- Yumpin' Yarley -- Midnight -- Epitaph to Jones'y -- Bush camels.
Keywords: Horses -- Fiction; Australia -- Fiction